EVALUATING THE LOCATION OF REGIONAL RETURN CENTERS IN REVERSE LOGISTICS THROUGH INTEGRATION OF GIS, AHP AND INTEGER PROGRAMMING - Acar, Avni Zafer; Onden, Ismail; Kara, Karahan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Reverse logistics network problems are accepted as sophisticated research areas in the existing literature due to difficulties of the prediction of the material flow in the network and the conflicting objectives of minimizing total cost and energy consumption while maximizing customer satisfaction and control of the pollution. There are different approaches to dealing with the difficulties of the problem, yet these approaches overlook the geographical aspect of the problems. In this paper, a reversed network of a governmental organization is evaluated, with spatial decision criteria taken into account. A methodology is proposed that integrates Analytic Hierarchy Process, Geographic Information Systems and integer programming to determine the locations of the return centers and to deal with the complicated structure. Population, airport locations, maritime facilities, railroad lines and highway lines are accepted as the decision criteria. Based on these decision criteria, suitability levels of the candidate cities are calculated. A closed-loop supply chain is taken into consideration and reverse functions of the chain are evaluated with the proposed methodology. Finally, the locations of regional return centers are determined.